Storyboard: How Is The Effect For EFL Learners In Writing Skiil? - Siti Islamiati; Vika Megawati (Proceedings of The ICECRS, 2021)
This research aims to know the students’ ability in writing recount text of the eighth grade students’ of SMP Ulul Albab Islamic Full Day School in the academic year of 2018/2019 through storyboard technique. The study used quantitative pre-experimental design. The subjects of the research were 25 students of VIII-C of SMP Ulul Albab Islamic Full Day School. The data were gained through pre-test and post-test. The result of the students’ scoring pre-test and post-test showed that storyboard technique develops the students’ writing ability in writing recount text. It can be seen from the mean score in pre-test were 70.56 and the post-test score were 82.72. The data were analysed by using t-test. The result of calculation showed that in the significance degree of level 5%, the value of t-count is higher than t-table (15.01 > 1.71). It means that there is effect of using storyboard technique in students’ writing ability especially writing recount text. In addition, the use of storyboard technique was able to improve the students’ achievement in writing